Q-switched erbium doped fiber laser based on single and multiple walled carbon nanotubes embedded in polyethylene oxide film as saturable absorber - Ahmed, M.H.M.; Ali, N.M.; Salleh, Z.S.; Rahman, Aizat A.; Harun, Sulaiman Wadi; Manaf, M.; Arof, Hamzah (Elsevier, 2015)
A passive, stable and low cost Q-switched Erbium-doped fiber laser (EDFL) is demonstrated using both single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs), which are embedded in polyethylene oxide (PEO) film as a saturable absorber (SA). The film is sandwiched between two FC/PC fiber connectors and integrated into the laser cavity for Q-switching pulse generation operating at wavelength of 1533.6 am. With SWCNTs, the laser produces a stable pulse train with repetition rate and pulse width ranging from 9.52 to 33.33 kHz and 16.8 to 8.0 is while varying the 980 am pump power from 48.5 mW to 100.4 mW. On the other hand, with MWCNTs, the repetition rate and pulse width can be tuned in a wider range of 6.12-33.62 kHz and 9.5- 4.2 mu s, respectively as the pump power increases from 37.9 to 120.6 mW. The MWCNTs produce the pulse train at a lower threshold and attain a higher repetition rate compared to the SWCNTs. This is due to thicker carbon nanotubes layer of the MWCNTs which provides more absorption and consequently higher damage threshold. The Q-switched EDFL produces the highest pulse energy of 531 nJ at pump power of 37.9 mW with the use of MWCNTs-PEO SA. (C) 2014 Elsevier Ltd. All rights reserved.